ANALISIS PENGARUH KECERDASAN INTELEKTUAL TERHADAP KEMAMPUAN AKUNTANSI DENGAN KECERDASAN EMOSIONAL DAN SPIRITUAL SEBAGAI PEMODERASI - Ria Manurung (Jurnal Keuangan dan Bisnis, 2018)
This research conducted to obtain empirical evidence of the influence of intellectual intelligence in accounting with emotional and spiritual intelligence as moderating variables. The research method used is descriptive quantitative with explanatory descriptive.For the use of data analysis consists of descriptive analysis, classical assumption test and verification analysis with the method of Moderated Regression Analysis (MRA). This study is a census study with homogeneous and limited population of 92 students, all students of Accounting Graduate Program at UNSOED. Conclusion of research result that is: (1) Intellectual intelligence have influence either positively or signifikan to accountancy. Thus intellectual intelligence can lead students to more easily understand accounting, (2) Intellectual intelligence can be strengthened by emotional intelligence on accounting both positively and significantly. (3) Spiritual intelligence can strengthen the influence of intellectual intelligence on accounting both positively and significantly.